Pushing Boundaries. New Directions in Contemporary Latin America-Middle East History - Balloffet, Lily; Camacho Padilla, Fernando; Stites Mor, Jessica (Anuario de Historia de América Latina, 2019)
This dossier addresses some of the lesser-explored historical legacies of the Cold War by delving into the newly emerging landscape of Middle East-Latin American relations of this period. Informing this investigation of geopolitical power and concomitant South-South dialogues that coalesced as part of that Cold War reality, the dossier brings together work that not only transgresses the typical boundaries between area studies of these regions but also pushes for a departure from the way in which Middle East-Latin American relations have often been relegated to and siloed within specific subfields of historical consideration, such as the study of the migration of Arabic-speaking peoples or the field of international relations. The dossier takes advantage of the ability to present several distinctive case studies in order to raise a challenge to historians of this period to broaden their contextualization of the relations between the two regions and to reposition Middle East-Latin American ties within a more complex historical framework of interaction and exchange.
Keywords: South-South Relations, Cold War, Middle East, Latin America, Historiography, Historical Methodology.